IMPLEMENTASI DAN PENGUJIAN SISTEM PENDAFTARAN SISWA PADA SMK KESEHATAN MAHARISHI DENGAN FRAMEWORK LARAVEL - Ni Luh Gede Pivin Suwirmayanti; Ni Kadek Sukerti; I Wayan Sumiarta (LPPM STMIK El Rahma Yogyakarta, 2020)
Maharishi Health Vocational School is one of the Educational Institutions in Bali, precisely in the City of Gianyar. In improving the quality of service to the general public, especially to prospective new students, a computerized system is needed, one of which is by creating a PSB or Registration process for new students that is not limited by place, time and energy. Until now Maharishi Health Vocational School still uses a manual system to register prospective students, so prospective students must, queue in registering at school. To increase the registration of prospective new students so that it runs smoothly and prospective new students do not need to queue in registering and make it easy to get information from schools, the means that can be used to overcome these problems is the use of an online registration system. This system will help prospective students, especially those who have great distances to go to school, can register online. So that makes the basis for researchers to create web-based new student registration applications with the concept of MVC (Model View Control) using the laravel framework. The method used in the development of this system is Waterfall and its design uses UML (Unified Modeling Language). The test results use the Black Box Testing method to ensure that the prospective student registration process is in accordance with the desired scenario, and student data and test scores can be stored in a database. Meanwhile information on prospective students who have passed or failed can be sent to all prospective students through the announcement menu. The process of registering prospective students and new students is expected to be done in a short time and can help the process of enrolling new students at the Maharishi Vocational Health School.